Sutureless Fixation of Amniotic Membrane for Therapy of Ocular Surface Disorders - Kotomin, Ilya; Valtink, Monika; Hofmann, Kai; Frenzel, Annika; Morawietz, Henning; Werner, Carsten; Funk, Richard H. W.; Engelmann, Katrin (PLOS ONE, 2015)
Amniotic membrane is applied to the diseased ocular surface to stimulate wound healing and tissue repair, because it releases supportive growth factors and cytokines. These effects fade within about a week after application, necessitating repeated application. Generally, amniotic membrane is fixed with sutures to the ocular surface, but surgical intervention at the inflamed or diseased site can be detrimental. Therefore, we have developed a system for the mounting of amniotic membrane between two rings for application to a diseased ocular surface without surgical intervention (sutureless amniotic membrane transplantation). With this system, AmnioClip, amniotic membrane can be applied like a large contact lens. First prototypes were tested in an experiment on oneself for wearing comfort. The final system was tested on 7 patients in a pilot study. A possible influence of the ring system on the biological effects of amniotic membrane was analyzed by histochemistry and by analyzing the expression of vascular endothelial growth factor-A (VEGF-A), hepatocyte growth factor (HGF), fibroblast growth factor 2 (FGF 2) and pigment epithelium-derived factor (PEDF) from amniotic membranes before and after therapeutic application. The final product, AmnioClip, showed good tolerance and did not impair the biological effects of amniotic membrane. VEGF-A and PEDF mRNA was expressed in amniotic membrane after storage and mounting before transplantation, but was undetectable after a 7-day application period. Consequently, transplantation of amniotic membranes with AmnioClip provides a sutureless and hence improved therapeutic strategy for corneal surface disorders. Trial Registration ClinicalTrials.gov NCT02168790